2021
DOI: 10.1002/cnr2.1313
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐marker immunohistochemical assessment of muscle‐invasive bladder cancer: Is there prognostic significance?

Abstract: Background Bladder cancer is the ninth most common cancer worldwide, and the third most common cancer in Lebanon. Immunohistochemistry (IHC) has been used to stratify muscle‐invasive bladder cancer (MIBC) into different subtypes. However, to our knowledge, there exists no study that investigates the use of this low‐cost technique to predict prognosis in bladder cancer patients in our region. Aim To examine the feasibility of low‐cost triple‐marker IHC assessment for MIBC subtyping in order to predict patients'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In our study, we did not observe consistent differences in terms of OS and CSS between the molecular subtypes obtained through surrogate IHC markers of any kind, in keeping with previous studies [ 16 , 24 , 29 , 30 , 31 , 32 , 33 ]. Serag-Eldien et al [ 34 ] applied a CK5/6/GATA3 classifier to their cohort of 80 BCs of any grade and stage and reported a trend of better OS and PFS for luminal MIBCs, although no statistical significance was achieved, in line with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we did not observe consistent differences in terms of OS and CSS between the molecular subtypes obtained through surrogate IHC markers of any kind, in keeping with previous studies [ 16 , 24 , 29 , 30 , 31 , 32 , 33 ]. Serag-Eldien et al [ 34 ] applied a CK5/6/GATA3 classifier to their cohort of 80 BCs of any grade and stage and reported a trend of better OS and PFS for luminal MIBCs, although no statistical significance was achieved, in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, in the study by Olkhov-Mitsel et al, basal (CK5/6+/GATA3-) MIBCs were independent predictors of worse disease-specific survival as compared to urothelial-like (CK5/6-/GATA3+/p16-) tumors ( p = 0.033) [ 31 ]. In keeping with this, specimens enriched with a luminal (CK5/6- and/or CK14-/GATA3+) phenotype showed higher PFS ( p = 0.032) in a cohort of MIBCs mostly treated with adjuvant cisplatin-based chemotherapy [ 30 ].…”
Section: Discussionmentioning
confidence: 83%
“…In a recent study, Labban et al classified their cohort of 64 MIBCs into Lum (GATA3+/CK5/6−/CK14−, 56.7%) and DP (GATA3+/CK5/6 and/or CK14+, 43.3%), with the former being significantly associated with a better PFS ( p = 0.039) [ 77 ]; the authors speculated that their DP tumors could be a surrogate marker for more aggressive biology, possibly due to an undisclosed P53-like signature [ 78 ]. Conversely, the CK5/6+/GATA3+ DP subtype identified in the MIBC cohort assessed by Bejrananda et al showed a significantly higher OS of 42.8% as compared to other subgroups [ 30 ].…”
Section: Ihc-based Molecular Subtypesmentioning
confidence: 99%
“…In the study by Olkhov-Mitsel et al, SD-UCs yielded the highest levels of heterogeneity with 47.7% cases classified as Bas, 31.8% as Uro, and 20.5% as GU [ 26 ], in keeping with the findings from a previous study by Sjodahl et al, with most SD-UCs clustering into the SCCL (Bas) (44%) and UroB (25%) subtypes [ 22 ]. The only SD-UC case in the cohort analyzed by Labban et al expressed both luminal and basal markers [ 77 ].…”
Section: Assessment Of Ucs With Divergent Differentiation and Histolo...mentioning
confidence: 99%